Creative And Innovative Strategies To Improve The Competitiveness Of Siomay Sellers In Sorong Regency - Magdalena Boga; Elisabeth Bhebhe Lalu (Journal of Innovative and Creativity, 2025)
This study aims to identify and analyze the creative and innovative strategies implemented by siomay-selling MSMEs in Sorong Regency to increase their competitiveness amidst market pressures and competition in the fast-food industry. This study used a qualitative approach with a case study method on four siomay entrepreneurs, identified as AN, BD, MR, and YS. Data collection techniques included field observation, in-depth interviews, and documentation. The results showed that each entrepreneur had a different approach in implementing their strategy. AN focused on innovation using local seafood-based raw materials, BD prioritized digitalization and visual branding, MR implemented a community-based collaborative model, while YS built a brand narrative through cultural and social media approaches. The strategies implemented included aspects of product, service, packaging, promotion, and social engagement, all tailored to local market characteristics. The study also found that successful innovation does not always depend on large capital, but on adaptability, market reflection, and a willingness to continue learning. Furthermore, external support such as training and mentoring has also been shown to strengthen the ability of MSMEs to design relevant and sustainable strategies. These findings confirm that creativity and innovation are important foundations for MSMEs in building competitive advantages based on local wisdom.